SIGNIFICANCE OF SERUM AMYLOID A FOR THE COURSE AND OUTCOME OF SARS-COV-2 INFECTION - Jegorović, Boris (Medicinski podmladak, 2023)
The occurrence of a new coronavirus, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), quickly became a global threat after it had spread across the continents in just a few months. Over the next three years, it caused infections in over 646.6 million people and resulted in over 6.6 million deaths. As a novel disease, Coronavirus Disease 19 (COVID-19) became the subject of intensive research. Due to various clinical manifestations of the infection with possible fatal outcomes, it became evident that a finer understanding of COVID-19 pathogenesis, clinical manifestations, and complications is necessary. Investigation of acute-phase reaction as a component of the immune system response to infection can be very helpful. Serum amyloid A (SAA) was investigated for this purpose as one of the acute-phase reactants primarily synthesized by the hepatocytes in response to pro-inflammatory cytokines. It has been found that elevated SAA levels were independent factors for gastrointestinal manifestations and liver injury during COVID-19 but also one of the factors in COVID-19-associated coagulopathy. Studies showed that SAA levels positively correlate with disease severity and prognosis. Patients with severe infection demonstrated significantly higher levels of SAA. Higher SAA levels were observed in COVID-19 patients with chronic diseases such as diabetes mellitus, hypertension, cerebrovascular diseases, and obesity, all recognized as independent risk factors for critical disease and poor prognosis. Patients with COVID-19 who died had higher levels of SAA than survivors. This short review will summarize current studies and knowledge about SSA in COVID-19, its role in the pathogenesis of SARS-CoV-2 infection, and its clinical usefulness in COVID-19 patients.
Keywords: serum amyloid A; SARS-CoV-2; COVID-19; fatal outcomes